2021
DOI: 10.1038/s41598-021-81484-1
|View full text |Cite
|
Sign up to set email alerts
|

High waist circumference rather than high body mass index may be a predictive risk factor for the longer disease duration of chronic spontaneous urticaria

Abstract: In a previous study, we found that higher waist circumference (WC) and higher body mass index (BMI) both increase the risk of chronic spontaneous urticaria (CSU). The aim of this study was to determine whether WC and BMI also increase the duration of CSU. We used multivariable Cox proportional hazards models to determine the hazard ratio (HR) for longer disease duration (longer than 3 years) according to WC and BMI. A total of 52,667 subjects were enrolled and their mean age was 54.5. After adjustments for oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
4
0
4
Order By: Relevance
“…A possible mechanism to explain the association between obesity and CSU is the concurrent elevation of systemic inflammatory markers in visceral obesity and CSU. Additionally, emerging evidence demonstrates that waist circumference, an indirect measure of visceral fat, may have better predictive utility in understanding factors associated with CSU duration compared with total body fat [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism to explain the association between obesity and CSU is the concurrent elevation of systemic inflammatory markers in visceral obesity and CSU. Additionally, emerging evidence demonstrates that waist circumference, an indirect measure of visceral fat, may have better predictive utility in understanding factors associated with CSU duration compared with total body fat [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Japanese and Mongolian scientists have shown that polymorphism of TaqI, BsmI, FokI and ApaI genes with vitamin D receptors is associated with chronic spontaneous urticaria [17,23].…”
Section: Results Discussionmentioning
confidence: 99%
“…However, Korean researchers have found that high waist circumference [17] rather than high body mass index [18] may be a prognostic factor in the long-term risk of chronic spontaneous urticaria. They used multivariate Cox proportional risk models to determine the risk factor for longerterm illness (more than 3 years) according to waist circumference and body mass index.…”
Section: Results Discussionmentioning
confidence: 99%
“…Auch im Vergleich zu gesunden Kontrollprobanden konnte ein signifikant höheres Auftreten von (zentraler) Adipositas, Diabetes mellitus, Hyperlipidämie und Hypertonie festgestellt werden – die allesamt zu der Definition eines metabolischen Syndroms zählen 34 55 56 59 60 . Zudem werden signifikante Auswirkungen der genannten Komorbiditäten auf die klinische Ausprägung oder die Krankheitsdauer der CSU beschrieben 43 47 51 58 62 . Zuletzt kann ein veränderter metabolischer Status sogar mit einem schlechteren therapeutischen Ansprechen der CSU assoziiert sein 46 54 61 .…”
Section: Assoziation Zwischen Csu Und Metabolischen Erkrankungenunclassified
“…So zeigte sich im Gegensatz zu der südkoreanischen Studie von Trinh et al bei einem Vergleich von 52 po lnischen CSU-Patienten mit 43 Kontrollen keine signifikanten Unterschiede im BMI oder in der Adiponektin-Konzentration [54,63]. In der multizentrisch durchgeführten Untersuchung einer französischen Kohorte konnte nach Einschluss von 278 CSU-Patienten zwar eine hohe Prävalenz von Adipositas festgestellt werden, jedoch zeigte sich kein Einfluss hierdurch auf die Krankheitsschwere oder einen erhöhten Antihistaminika-Bedarf der CSU-Patienten [45], wie in anderen Publikationen beschrieben wurde [46,58,62].…”
Section: Assoziation Zwischen Csu Und Metabolischen Erkrankungenunclassified